AB0280 Imnunogenicity and clinical practice in patients treated with anti-tnf therapy. (23rd January 2014) - Alcocer, P.; Plasencia, C.; Pascual, D.; Garcia Carazo, S.; Franco, K. N.; Cagijas, D.; Lojo, L.; Bonilla, G.; Nuño, L.; Villalba, A.; López Casla, M. T.; Balsa, A.; et al.
Abstract : Background: Biological therapy (BT) is very effective in patients with rheumatoid arthritis (RA). Although there are tools to measure treatment response, they have limitations making necessary to get more objective parameters to improve clinical evaluation. The immunogenicity of anti-TNF therapy has been associated with lack of efficacy, side effects and decreased survival. In our hospital, the monitoring of immunogenicity is considered as an additional tool to clinical practice since 2010, helping in treatment decisions as switching medication, dose reduction or even discontinuation. Objectives: To asses the benefit of using the immunogenicity as a complementary tool in clinical practice of RA patients and to analyse differences in outcome measures before and after the use of immunogenicity. Methods: We included 134 RA patients who started a 1st biologicbetween the years 2005-2012. The patients were divided into two time periods to analyze differences in clinical management after to monitor the BT immunogenicity: 1st period (1P) from 2005 to 2009 with 89 patients and 2nd period (2P) from 2010 to 2012 with 45 patients. The used drugs were infliximab, adalimumab, etanercept, rituximab, tocilizumab, abatacept and certolizumab. The clinical activity was measured by DAS28 and the clinical improvemet by delta-DAS28. The drug and anti-drug antibodies (ADA) serum levels were measured by ELISA. Statistical analysis was performed using SPSS 11.0. Results: A similar control of disease activity is achieved in both periods, but in the 2P, where in addition to the usual measures we use immunogenicity monitoring, shows that we are more cost-effective, taking decisions earlier and more accurate. These data suggest that immunogenicity can help to improve and personalize the clinical manage of patients treated with biologicals. Conclusions: A similar control of disease activity is achieved in both periods, but in the 2P, where in addition to the usual measures we use immunogenicity monitoring, shows that we are more cost-effective, taking decisions earlier and more accurate. These data suggest that immunogenicity can help to improve and personalize the clinical manage of patients treated with biologicals. Disclosure of Interest: None Declared